THE EFFECT OF SOCIAL MEDIA PROMOTION AND FACILITIES ON VISITING DECISIONS ON ANDALUS TOURISM - Wahyuni, Sri; Putri, Librina Tria; Azhari, Azhari (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of social media promotion and facilities jointly and individually on the decision to visit Andalus tourism objects. The analysis used in this study is multiple linear regression analysis with the number of respondents as many as 98 people. Hypothesis testing is done by f test (simultaneous) and t test (partial). Based on the results of the study, it can be concluded that the promotion of social media and facilities simultaneously influences the decision to visit Andalus tourism objects. Furthermore, based on a partial test, promotion of social media and facilities affect the decision to visit Andalus tourism objects. The close relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable of 67.60 %.